Definition of oligometastatic esophagogastric cancer and impact of local oligometastasis-directed treatment: A systematic review and meta-analysis. (May 2022) - Kroese, Tiuri E.; van Laarhoven, Hanneke W.M.; Nilsson, Magnus; Lordick, Florian; Guckenberger, Matthias; Ruurda, Jelle P.; D'Ugo, Domenico; Haustermans, Karin; van Cutsem, Eric; van Hillegersberg, Richard; van Rossum, Peter S.N.
Abstract: Background: Local treatment (metastasectomy or stereotactic radiotherapy) for oligometastatic disease (OMD) in patients with esophagogastric cancer may improve overall survival (OS). The primary aim was to identify definitions of esophagogastric OMD. A secondary aim was to perform a meta-analysis of OS after local treatment versus systemic therapy alone for OMD. Methods: Studies and study protocols reporting on definitions or OS after local treatment for esophagogastric OMD were included. The primary outcome was the maximum number of organs/lesions considered OMD and the maximum number of lesions per organ (i.e. 'organ-specific' OMD burden). Agreement was considered to be either absent/poor (< 50%), fair (50%–75%), or consensus (≥ 75%). The secondary outcome was the pooled adjusted hazard ratio (aHR) for OS after local treatment versus systemic therapy alone. The ROBINS tool was used for quality assessment. Results: A total of 97 studies, including 7 study protocols, and 2 prospective studies, were included. OMD was considered in 1 organ with ≤ 3 metastases (consensus). 'Organ-specific' OMD burden could involve bilobar ≤ 3 liver metastases, unilateral ≤ 2 lung metastases, 1 extra-regional lymph node station, ≤ 2 brain metastases, or bilateral adrenal gland metastases (consensus). Local treatment for OMD was associated with improved OS compared with systemic therapy alone based on 6 non-randomized studies (pooled aHR 0.47, 95% CI: 0.30–0.74) and for liver oligometastases based on 5 non-randomized studies (pooled aHR 0.39, 95% CI: 0.22–0.59). All studies scored serious risk of bias. Conclusions: Current literature considers esophagogastric cancer spread limited to 1 organ with ≤ 3 metastases or 1 extra-regional lymph node station to be OMD. Local treatment for OMD appeared associated with improved OS compared with systemic therapy alone. Prospective randomized trials are warranted. Highlights: Uniform definition of oligometastatic esophagogastric cancer is lacking. 1 organ with ≤3 metastatic lesions was considered oligometastatic (consensus). Local treatment for oligometastases yields favorable overall survival. Serious risk of bias in includes studies (all non-randomized).